Alineamiento y aplicaciones del neutrógrafo del reactor Rp-10 - López y Cols., Alcides (2019)
We present here the process of optical axis alignment of the neutrographic system with the optical axis of the neutron beam from window 4 of the nuclear reactor rP-10. This process is done with the aid of a radiographic technique, which facilitates locating the optical axis of the neutron beam in space by a photographic record, thus allowing for later alignment of the neutrograph. The high neutronic absorption coefficient of light chemical elements and the high contrast of materials with similar density are an advantage for applications. The neutrograph has a wide variety of applications, among them: the analysis of nuclear fuels, the detection of hydrogenated and organic materials, the detection of flaws in turbine blades, the detection of corrosion in aircraft components, quality control of ceramic materials, detection of drugs and explosive materials (used in the pyrotechnic and ammunition industry), the study of archaeological materials, the detection of lubricating films in bearing systems, as well as dynamic processes of lubrication and combustion, among others. in this work we present a variety of examples of applications with the reactor rP-10.